Traumatic Brain Injury Cases Through Emergency Department During Covid-19 Pandemic Era 2020 In Adam Malik General Hospital Medan - Mahyudanil, Mahyudanil; Sinaga, Patrice LWY; Irsyad, M. Ari; Faisal, Faisal; Hutagalung, Tommy Rizky (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2021)
Abstract Introduction: Coronavirus disease 2019 (COVID-19) has been infecting nearly 800.000 individuals of all ages in 31 March 2020. Based on Harvard Medical school experience, almost over 80% of patients have switched to telemedicine services. In Indonesia, there are almost 1,22 million cases with recovery of 1 million case and the death of 33.183 cases. In North Sumatera, the COVID-19 cases occurred in 22.999 cases and the recovery of 19.758 cases with death of 786 cases. Here, we report the trend of traumatic brain injury (TBI) cases in pandemic era 2020 in our institution in Adam Malik General Hospital, Medan, North Sumatera. Method: This retrospective observational study reported 343 TBI cases from January 2020 to December 2020. January 2020 to March 2020 regarded as pre pandemic and April 2020 to December 2020 as the pandemic era. Results: There is significant decrease of traumatic brain injury patients from March 2020 to April 2020. It was 61% decrease in patients admission to our Emergency Department (ED). Demographically, male patients in productive age group and mild TBI has the most common presentation to our ED. Discussion: There is significant decrease of patients with TBI in our institution. The number of cases was declining from 55 patients on January to 21 patients on April. This also occurred concurrently with the start of social distancing in Indonesia on April 2020 and the civilian suggested to stay at home during this period. This decline was also found in other countries, like Massachusetts, USA and India. Conclusion: We reported significant decrease in traumatic brain injury cases in Adam Malik General Hospital during COVID-19 pandemic era in 2020. Neurosurgeons and Residents of Neurosurgery have to be cautious in assessing the TBI patients to limit the spread of COVID-19 in ED.